The Effect of Liquidity, Leverage and Company Size on Profitability - Supitriyani; Khairul Azwar; Siti Rahmayani Siregar; Astuti Astuti; Elly Susanti (INTERNATIONAL JOURNAL OF TRENDS IN ACCOUNTING RESEARCH, 2020)
The purpose of this research are to determine the description of liquidity, leverage, company size and profitability and than description of the effect of liquidity, leverage, and company size on the profitability at company Sub Sector Hotel, Restaurant, and Tourism Listed in BEI either simultaneously or partially. This research uses descriptive qualitative and quantitative. This research found the results that liquidity, company size, and profitability increased, while average leverage tended to decrease. Either simultaneously, liquidity, leverage, and company size has positive and not significant effect on profitability. T-test results that liquidity has a positive and not significant effect, results that leverage have a negative and not significant, results that company size has a positive and significant effect on profitability. liquidity, leverage, and company size able to explain most of profiability in Companies Sub Sector Hotel, Restaurant, and Tourism.